2010
DOI: 10.1039/b915816b
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic pathways of selenium metabolism and excretion in mice under different selenium nutritional statuses

Abstract: The selenoprotein, cellular glutathione peroxidase (cGPx), has an important role in protecting organisms from oxidative damage through reducing levels of harmful peroxides. The liver and kidney in particular, have important roles in selenium (Se) metabolism and Se is excreted predominantly in urine and feces. In order to characterize the dynamics of these pathways we have measured the time-dependent changes in the quantities of hepatic, renal, urinary, and fecal Se species in mice fed Se-adequate and Se-defici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 28 publications
1
25
0
1
Order By: Relevance
“…TMSe is now considered to be a less significant metabolite (Francesconi, 2006). More recently it has been shown that after Se supplementation to mice the element is metabolized mainly in the liver and kidney (Suzuki et al, 2010). Excess Se was associated with selenosugar in the liver, transported to the kidney and the excess amount was excreted mainly as a selenosugar in urine.…”
Section: Selenium Content and Glutathione Peroxidases Activities In Dmentioning
confidence: 99%
“…TMSe is now considered to be a less significant metabolite (Francesconi, 2006). More recently it has been shown that after Se supplementation to mice the element is metabolized mainly in the liver and kidney (Suzuki et al, 2010). Excess Se was associated with selenosugar in the liver, transported to the kidney and the excess amount was excreted mainly as a selenosugar in urine.…”
Section: Selenium Content and Glutathione Peroxidases Activities In Dmentioning
confidence: 99%
“…With mass spectrometry, there can be many problems for quantification: proteins may not be completely tryptically digested, the ionization efficiencies of ESI-MS can fluctuate depending on the matrices and peptides, and the intensities of MALDI-MS signals can fluctuate depending on the area irradiated by the laser. Quantification of the relative abundances of peptides or proteins by using mass spectrometry can be achieved through the use of chemical labeling methods involving the derivatization of selected amino acid residues with isotopically ( 2 H, 13 C, 15 N, 18 O) modified reagents, such as ICAT (isotope-coded affinity tag),not require protein standards or specific reagents are needed.…”
Section: Introductionmentioning
confidence: 99%
“…From the viewpoint of atomic mass spectrometry, ICPMS has been used to quantify metal proteins such as metallothionein and selenoproteins. [11][12][13][14][15][16] In addition to metallic and metalloid elements, non-metal elements, such as sulfur (S) and phosphorus (P), are considered to be important for protein quantification. In particular, S is a key element for protein and peptide quantification because most proteins contain 2 S-containing amino acids, cysteine and methionine; cysteine is present in 96.6% of human proteins, and methionine is present in 98.8%.…”
Section: Introductionmentioning
confidence: 99%
“…The functions and mechanisms of Se-dependant GSH-Px in maintaining human health and strengthening life have been studied and reviewed intensively [1][2][3][4][5][6], especially in antioxidant activity for aging defending, against cardiovascular diseases and cancers such as lung tumor [7], uterine cervix [8] and prostate cancers [9]. The trace but essential of selenium in nutrition indicates that either overdose or insufficiency of dietary selenium might result in harmful risk.…”
Section: Introductionmentioning
confidence: 99%